Increased risk of angiosarcoma secondary to cancer radiotherapy: Case series and review of the treatment options. Issue 2 (5th February 2020) - Goldust, Mohamad; Giulini, Mario; Weidenthaler‐Barth, Beate; Gupta, Mrinal; Grabbe, Stephan; Schepler, Hadrian
Abstract: Angiosarcomas (ASs) are aggressive tumors of vascular endothelial origin, occurring sporadically or in association with prior radiotherapy or chronic lymphedema. With only 1–5% of all sarcomas, the incidence seems low, but for the affected patient due to the extremely poor prognosis and the limited treatment options, the fate is often inevitable. Radiotherapy, chemotherapy, or "target therapy" have been used in the management of AS, but represent individual case decisions without lasting evidence. Over the past few years, breast‐conserving surgery followed by radiation therapy, known as breast‐conserving therapy (BCT), is being employed as a standard treatment for early‐stage breast cancer, but there has been an increase in reports of AS following BCT. We report two cases of AS following BCT and one case of primary AS involving the lower limb.